2019
DOI: 10.5222/buchd.2019.34635
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia Among Children in a Single University Hospital

Abstract: Objective: Anemia is a common public health issue, causing an increase in mortality and morbidity, especially in pregnant women and children. WHO reported the prevalence of anemia in preschool children as 47.4%, and incidence of anemia is gradually increasing. Iron deficiency is responsible for approximately 50% of cases with anemia. This study aims to determine the prevalence of anemia and the underlying causes of anemia in pediatric patients who were admitted to a reference hospital. Method: This cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…In Spanish and South-East Asian adolescents, a higher prevalence of iron deficiency was reported compared with our results (13,14). Studies of Turkish children reported that the iron deficiency rate was between 15.7% and 28%, higher in girls than in boys; however, the rate was higher in boys compared with girls early in life (15,16). According to our findings, the lower ferritin levels were obtained compared to the results of the National Health and Nutrition Examination Survey (NHANES), and Korean NHANES (2010-2012) (17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…In Spanish and South-East Asian adolescents, a higher prevalence of iron deficiency was reported compared with our results (13,14). Studies of Turkish children reported that the iron deficiency rate was between 15.7% and 28%, higher in girls than in boys; however, the rate was higher in boys compared with girls early in life (15,16). According to our findings, the lower ferritin levels were obtained compared to the results of the National Health and Nutrition Examination Survey (NHANES), and Korean NHANES (2010-2012) (17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…2012 yılında Sivas'ta 1-15 yaş grubunda benzer şekilde retrospektif olarak yapılan bir çalışmada anemi prevalansı %5,9 olarak bulunmuştur (15). Samsun ilinde 2017-2018 yıları arasında üniversite hastanesine başvuran 0-15 yaş grubu çocuklarla yapılan bir çalışmada ise anemi prevalansı %8,2 olarak bulunmuştur (16). İstanbul'da 2011 yılında sünnet için başvuran 450 erkek çocuk ile retrospektif olarak yapılan çalışmada ise anemi prevalansı %6,4 olarak bulunmuştur (17).…”
Section: Discussionunclassified
“…Anemi nedenlerine bakıldığında demir eksikliği anemisi tüm dünyada olduğu gibi ülkemizde de ilk sırada yer almaktadır. Samsun ilinde yapılan benzer bir çalışmada demir eksikliği anemisi oranı %28 olarak bulunmuştur (16). Ülkemizde poliklinik kayıtları incelenerek adölesanlar üzerinde yapılan benzer bir çalışmada demir eksikliği anemisi prevalansı %17-30 oranında bulunmuştur (14).…”
Section: Discussionunclassified
“…Anemia is a common public health problem that causes increased mortality and morbidity, especially in pregnant women and children. Anemia prevalence is 47.4% in preschool children worldwid and it is the most important reason for nutritional iron deficiency in children (1).…”
Section: Introductionmentioning
confidence: 99%